Reorientasi Pendidikan Islam dalam Menguatkan Masyarakat Plural - Fathurrohman, Fathurrohman (Proceedings of Annual Conference for Muslim Scholars, 2019)
a reorientation of Islamic education needs to be done because with that the strengthening in a plural society can be achieved. a reorientation of Islamic education needs to be done because with that the strengthening in a plural society can be achieved. Through socially and religiously aromatic activities, harmony in a plural society will also be created and well-entrenched. Another thing needed to strengthen a plural society is to adopt an attitude of tolerance which is included as a major supporter in building a strong plural society. The attitude of solidarity also needs to be applied in order to maintain wholeness in a plural society, because with that attitude when we live in society, we will certainly see everything that can be related to individuals and even to social problems. For this reason, a reorientation of Islamic education is needed so that strengthening in a plural society can be carried out well